2019
DOI: 10.4166/kjg.2019.74.3.142
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Asymptomatic Colon Diverticulosis

Abstract: Backgrounds/Aims: The etiology of colon diverticulosis is related to a range of genetic, biological, and environmental factors, but the risk factors for asymptomatic diverticulosis of the colon are unclear. This study examined the risk factors for asymptomatic colon diverticulosis. Methods: This retrospective study included examinees who underwent a colonoscopy for screening at the health check-up center of SAM Hospital between January 2016 and December 2016. The examinees with colon diverticulosis found by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
2
11
2
2
Order By: Relevance
“…For example, a series of >62,000 colonoscopies performed in China demonstrated <2% of the population had diverticulosis, but >85% was right-sided 15 . Similar studies from Korea and Taiwan have demonstrated higher prevalence, 13-15%, with preserved right-sided dominance 16,17 . The underlying biology behind the anatomic variation is unknown, but right-sided diverticulosis intuitively seems less likely to be due to constipation and mechanical stress, given the liquid nature of stool in the right colon.…”
Section: Epidemiologysupporting
confidence: 70%
“…For example, a series of >62,000 colonoscopies performed in China demonstrated <2% of the population had diverticulosis, but >85% was right-sided 15 . Similar studies from Korea and Taiwan have demonstrated higher prevalence, 13-15%, with preserved right-sided dominance 16,17 . The underlying biology behind the anatomic variation is unknown, but right-sided diverticulosis intuitively seems less likely to be due to constipation and mechanical stress, given the liquid nature of stool in the right colon.…”
Section: Epidemiologysupporting
confidence: 70%
“…While the presence of T2DM, hyperlipidemia, smoking status, and alcohol consumption were similar in patients with CD and the control group, HTA was significantly more frequent in patients with ADD. This study reported that moderate and severe fatty liver disease, as well as waist-hip ratio, were risk factors for ADD, highlighting the possible role of central obesity and NAFLD in the pathogenesis of ADD [18]. Contrary to these findings, Sahin et al [21] found that in elderly patients, diverticulosis is a negative predictor of liver steatosis.…”
Section: The Impact Of Nafld and Colonic Diverticulosis On Metabolic Syndromementioning
confidence: 62%
“…Nevertheless, NASH and cirrhosis that result from chronic inflammation typically develop in advanced age [23]. Colonic diverticulosis is also more common in Western countries, underlying the impact of Western diet, lifestyle, obesity, and MetS on development of CD [9,18,22]. Consequently, it appears that dietary habits and aging significantly influence the occurrence and severity of NAFLD and CD.…”
Section: The Impact Of Nafld and Colonic Diverticulosis On Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Diverticular disease (DD) is more prevalent in western countries but in Asia, diverticulosis is almost rare, though the prevalence has been increased recently along with the overall increase in prevalence throughout the world. 5 The current accepted causes of diverticula formation are the transmission of muscular contraction pressure to the wall of the colon, inducing the formation of diverticula usually at the weakest point of the wall where penetration of the blood vessels occurs. It is also considered as a multifactorial disease.…”
Section: Introductionmentioning
confidence: 99%